Integrated Assessment Services at The National Narcotics Agency of East Java: A Social Identity Perspective - Nur Aviatur Rohmatin; Vania Ardelia (International Conference on Psychology and Education (ICPE), 2025)
Drug abusers are people who use narcotics without permission or against the law. Based on data from drug abuse clients, the majority of drug abuse is committed by men. This study uses a qualitative research method with a case study approach. The purpose of this study is to conduct a review to understand and adjust issues related to human behavior based on existing theories and value comparisons in society. Based on the research results, it is known that integrated assessment services are very important to provide justice and law enforcement for drug abusers and users in the form of recommendations to carry out legal action or rehabilitation. This study is expected to provide a more in-depth description of the integrated assessment services provided by the East Java National Narcotics Agency specifically in the context of social identity theory.